Evaluation of Neospora caninum serodiagnostic antigens for bovine neosporosis. (April 2020) - Abdelbaky, Hanan H.; Nishimura, Maki; Shimoda, Naomi; Hiasa, Jun; Fereig, Ragab M.; Tokimitsu, Hiromi; Inokuma, Hisashi; Nishikawa, Yoshifumi
Abstract: Abortion and reproductive failure caused by Neospora caninum infection has a dramatic negative economic impact on the cattle industry. To date, no definitive serodiagnostic tool for assessing N. caninum abortion has been reported. In this study, we evaluated the diagnostic performance of numerous N. caninum antigens in relation to abortion in cattle. Five recombinant proteins with potential as diagnostic antigens (NcGRA6, NcGRA7, NcGRA14, NcCyP, and NcSAG1) were compared by indirect enzyme-linked immunosorbent assay (iELISA) using sera from mice and cattle experimentally infected with N. caninum . The best-performing three antigens (NcSAG1, NcGRA7, and NcGRA6) were evaluated by IgG-iELISAs to assess their utility in diagnosing Neospora abortion using sera from confirmed N. caninum -aborted dams based on immunohistochemical assays (IHC). Additionally, all samples were tested using a commercial N. caninum antibody competitive ELISA (cELISA). The iELISAs against both NcSAG1 and NcGRA7 could efficiently distinguish IHC positive and negative samples compared with iELISAs against NcGRA6 and the cELISA. Furthermore, antibody levels against NcSAG1 and NcGRA7 were significantly higher in aborting cows comparing with infected but non-aborted dams in a herd experiencing a Neospora abortion outbreak. Tracking the dynamics of antibody levels during pregnancy revealed a marked increase in NcSAG1- and NcGRA7-specific antibodies at the last trimester of pregnancy. In contrast, no marked differences in antibody levels against either antigen were noted in neurologically symptomatic calves compared with non-symptomatic infected calves. Our data suggests NcSAG1 and NcGRA7 as indicators for Neospora abortion. Highlights: Five Neospora potential diagnostic antigens were compared by iELISA. Higher levels of NcSAG1 and NcGRA7 antibodies were detected in aborting cows. Higher antibody levels against NcSAG1 and NcGRA7 at the delivery time were observed. No marked differences in antibody levels were noted in paralytic form of calves. A higher level of anti-NcSAG1 antibodies was associated with Neospora abortion.